COIN: A fast packet inspection method over compressed traffic. (1st February 2019) - Sun, Xiuwen; Li, Hao; Zhao, Dan; Lu, Xingxing; Hou, Kaiyu; Hu, Chengchen
Abstract: Matching multiple patterns simultaneously is a key technique in Deep Packet Inspection systems, such as firewall, Intrusion Detection Systems, etc . However, most web services nowadays tend to compress their traffic for less data transferring and better user experience, which has challenged the original multi-pattern matching method that work on raw content only. The straightforward solutions directly match decompressed data which multiply the data to be matched. The state-of-the-art works skip scanning some data in compressed segments, but still exist the redundant checking, which are not efficient enough. In this paper, we propose COmpression INspection (COIN) method for multi-pattern matching over compressed traffic. COIN does not recheck the patterns within compressed segment if it has been matched before, so as to further improve the performance of matching, we have collected real traffic data from Alexa top sites and performed the experiments. The evaluation results show that COIN achieves 20.3% and 17.0% in the average of improvement than the state-of-the-art approaches on the string and regular expression matching with real traffic and rule sets.